Self-efficacy and unwanted sexual intercourse: 'Reproductive health education programme for high-school students in Vojvodina' - Tomašević Tanja; Ukropina Snežana; Jovanović Vesna Mijatović; Kvrgić Svetlana; Čanković Sonja; Milijašević Dragana (Sciendo, 2022)
Studies have shown the importance of self-efficacy in the domain of risky sexual behaviour. The aim of this study was to examine the association of unwanted sexual intercourse among secondary-school students with socio-demographic factors and perceived self-efficacy, and to assess the effectiveness of the programme on reproductive health.